Union Actors and Socio-environmental Problems : the Trade Union Confederation of the Americas - Anigstein, Cecilia (2019)
Fil: Wyczykier, Gabriela. Universidad Nacional de General Sarmiento. Instituto de Ciencias; Argentina.